2011
DOI: 10.1007/s12291-011-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Bone Scan Findings and Serum Levels of Tumor Marker CA15-3 in Patients with Breast Carcinoma

Abstract: Breast cancer is one of the most frequent malignancies in the world. Available staging procedures to detect breast cancer are bone scan, chest X-ray, liver ultrasonography, computerized tomography, estimation of tumor markers like carbohydrate antigen (CA15-3) and carcino embryonic antigen. These procedures are expensive and may not be required in all cases. Out of 70 patients studied, 55 had normal CA15-3 and 15 had elevated levels of Ca15-3. Eight (14.5%) of the 55 patients with normal CA15-3 had abnormal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Breast cancer is the most common form of cancer in women and the second leading cause of death due to malignant disease in females after lung cancer [ 1 , 2 ]. In recent years, the incidence of breast cancer has significantly increased in both Eastern and Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the most common form of cancer in women and the second leading cause of death due to malignant disease in females after lung cancer [ 1 , 2 ]. In recent years, the incidence of breast cancer has significantly increased in both Eastern and Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Components of bodily fluids are ideal biomarkers for disease diagnosis because of their simplicity of detection. For example, the serum has long been considered a rich source of biomarkers, and several serum cancer biomarkers, such as cancer antigen 125 (CA125), carcinoembryonic antigen (CEA), and cancer antigen 15-3 (CA15-3), have been proposed [ 2 , 7 , 8 , 9 ]. However, serum protein biomarkers are often not sufficiently sensitive to be used for screening and early diagnosis because their levels reflect tumor burden [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone metastasis is very common in breast cancer affecting approximately 70% of patient (1,2). The detection of bone metastasis accurately reflects the prognosis and the early detection in the asymptomatic case may alert the clinician to the possible complications inherit in skeletal destruction (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It was found as the first breast cancer‐associated antigen in 1984 7. After decades of experimental research on it, investigators had found that CA15‐3 could be used as diagnostic and prognostic factor and could also provide valuable information during follow‐up 8, 9, 10, 11. Thus, measurement of CA15‐3 is significant for breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%